THE ROLE AND RESPONSIBILITIES OF THE INVESTIGATOR IN CRIMINAL PROCEEDINGS - Litvinova , Iryna; Perehinets, Tetyana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to examine the role and powers of an investigator in criminal proceedings with a view to defining his/her key function in conducting an investigation, ensuring justice and interacting with other participants to justice. Research methods: the author uses a comprehensive analysis of legal acts, scientific literature and practice of application of criminal procedure legislation. Results: the author has established that the investigator is a key figure in the pre-trial investigation and is responsible for a comprehensive, complete and impartial investigation of the circumstances of criminal proceedings. The investigator has broad powers that enable him or her to collect evidence, identify perpetrators, and take measures to ensure their presence in court. However, even when recognizing the achievements of the Criminal Procedure Code, it is necessary to recognize its shortcomings, in particular, in the issue of powers of investigators. Abuse of these powers can lead to illegal pressure on witnesses, illegal detentions and other violations. Some norms of the Criminal Procedure Code of Ukraine regarding the powers of the investigator require clarification and clear wording. Solving these problems requires an integrated approach. First, it is necessary to improve the legislation to eliminate ambiguities and gaps in the authority of the investigator. Secondly, systematic training and professional development of investigators should be carried out so that they have sufficient knowledge and skills for the correct application of the law. Thirdly, it is necessary to strengthen control over the activities of investigators by creating an effective supervision system that will prevent abuse and violations of the law. Discussion: an important aspect of the investigator’s activity is compliance with the principles of legality, objectivity, comprehensiveness and completeness of the investigation of the circumstances of criminal proceedings. The investigator is obliged to impartially investigate all the circumstances of the case, both incriminating and exculpatory, to give them an appropriate assessment and to make a lawful and reasonable decision. The current legislation of Ukraine, unfortunately, does not guarantee full procedural autonomy and independence of the investigator. To improve the situation, it is necessary to make changes to the legislation, clearly defining the concepts of "procedural independence" and "independence" of the investigator. This will increase the efficiency of the pre-trial investigation and ensure the legality and objectivity of procedural decision-making. Only in this way will it be possible to talk about respect for human rights and justice in the field of criminal justice.